Aczélhálóban: Adalék a kapcsolati tőke működésének megértéséhez - Sik, Endre (Szociológiai Szemle, 2024)
In paper I start with some explanations why in socialism politics was more network-oriented than it is under "normal" circumstances (under which it is network oreinted to a great degree). I argue that this was partly the consequence of a special feature of path dependent development of the post 56-revolution, i.e. the coming to power of a socialist politician (his name was György Aczél (in English Steel) who was a artist in netwroking. This historical accident (on top of the Hungarian network oriented culture and the special political circumstanes) created a fertile soil of the high inertia development of network capital which survived the transformation from socialism to capitalism which - partly due to the high inertia of network capital - retained the network oriented nature of pre-postsocialism.